Financial feasibility of a Central California greenhouse operation - Gilardi, Jonelle (My University, 2026)
This study evaluates the financial feasibility of establishing a one-acre greenhouse operation in California’s Sacramento Valley. This region offers favorable demand for locally grown and sustainable products, while also presenting challenges related to climate variability, rising input costs, and resource constraints. This creates the need for a structured feasibility assessment. The analysis combines market conditions, strategic planning and a ten-year net present value model. Market findings indicate a strong demand from home gardeners and landscapers, supported by Sacramento’s community emphasis on sustainability and local food systems. Strategic results highlight the importance of differentiation through climate-adapted offerings, horticultural expertise, and community engagement rather than competing directly with other retailers on price. Financial feasibility is assessed using projected revenues and costs. The baseline model produces a positive NPV, indicating expected financial viability. A sensitivity scenario with a 10% increase in variable costs results in a significant decrease in NPV, reflecting the importance of cost pressures and the narrow operating margins typical for small greenhouse operations. Overall, the greenhouse operation is feasible under anticipated market and cost conditions, but requires disciplined cost management, strategic positioning, and ongoing monitoring. This study provides a framework for evaluating similar small-scale horticulture ventures and identifies areas for future research related to financing options, product mix strategies and long-term sustainability.
Keywords: Financial feasibility; California horticulture; Central California greenhouse; Horticulture market; Greenhouse operation; Horticulture financial analysis